MY CONTRIBUTION TO THE DEVELOPMENT OF MY COUNTRY - MANZURA Oʻteniyazova Azatbayevna; SHAKHNOZABONU Baltaniyazova; ULZADA Baltabaeva; Orazbaeva Nilufar Daryabaevna (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about mentally mature, mentally strong, physically healthy young people an invaluable place for the development of the country, today and tomorrow, Uzbekistan today The theme of the role and power of youth in the creation of the Third Renaissance illuminated